Cambodian Agriculture in Transition : Opportunities and Risks - World Bank Group (World Bank, Washington, DC, 2015)
This report seeks to understand the successes, challenges and opportunities of Cambodia’s agricultural transformation over the past decade to derive lessons and insights on how to maintain future agricultural growth, and particularly on the government’s role in facilitating it. It is prepared per the request of the Supreme National Economic Council and the Ministry of Agriculture Forestry and Fisheries and is based on the primary farm data surveys from 2005 and 2013, and the secondary data from various sources. In 2013-2014, the agricultural growth slowed down to 1 percent from its average of 5.3 percent over 2004-2012. Is the country in transition to a slower agricultural growth? Cambodia can ill afford it because agricultural growth will be critical to continued poverty reduction in the country, given its large size in the economy. Market and private investment friendly policies and targeted public sector investments in irrigation, extension, and other ‘public good’ agricultural services, as feasible within the government’s total budget, can help secure continued robust agricultural growth. The remaining report is organized as follows. Chapter two presents key facts about Cambodia’s recent agricultural development using data from national accounts and various reports. Chapter three provides evidence from the field that explains the changes observed in the national accounts. Chapter four illustrates developments in farming systems, farm budgets, and farm incomes compared to nonfarm incomes. Chapter five presents a farm competitiveness analysis. Chapter six discusses the sources of past growth and their limitations and presents an analysis of (likely) future sources of agricultural growth. Chapter seven presents a long-term vision for the sector, while chapter eight simulates policies and the changes in farm incomes needed to realize this vision. Chapter nine discusses the policy agenda, with implementation details based on national and global experiences. Chapter ten concludes with a summary of the report and policy recommendations. Annexes present the methodology of the 2013 farm survey, detailed farm budgets by crop, projections of selected indicators, and results of the policy simulations.